Comparative studies of essential oils of Clausena anisata (Hook) using solvent-free microwave extraction and hydrodistillation methods - Ibraheem O. Lawal; Hilda Ajayi; Paul O. Dairo; Paul O. Ogunbamowo (AOSIS, 2019)
Background: Essential oils have been used for medical purposes because of their medicinal properties and are sourced from natural products. Aim: The comparative study of essential oils from Clausena anisata leaves obtained through two methods of extraction was undertaken. Setting: C. anisata leaves were collected from Akinsola village in Ido Local Government Area of Oyo State, Nigeria. Methods: Essential oil was extracted using the methods of solvent-free microwave extraction (SFME) and hydrodistillation (HD) and then analysed using gas chromatography coupled with mass spectrometer (GC-MS). Results: The result shows that the essential oils obtained from the leaves of C. anisata through SFME and HD are pale yellow and colourless, respectively. A higher oil yield of 5.2 mL/100 g was obtained through SFME compared to 3.7 mL/100 g obtained through HD. There was an abundance of monoterpenes in the oil obtained using HD, while sesquiterpenes were the dominant compounds in the oil extracted using SFME. Other compounds present were α-cubebene, α-copaene and α-pinene with 1091.63, 1091.64 and 979.35, respectively. Conclusion: The compounds obtained which are very important in the cosmeceutical and pharmaceutical industries, is dependent on the method of essential oil extraction.